ENTREPRENEURIAL COMPETENCE: THE PERCEPTIONS OF SCHOOL PRINCIPALS IN SECONDARY EDUCATION AND ITS IMPACT ON ENTREPRENEURSHIP EDUCATION - Faridah, Faridah; Ansar, Ansar (Lentera Pendidikan : Jurnal Ilmu Tarbiyah dan Keguruan, 2022)
This study explores perceptions of school principals in secondary education about entrepreneurial competence, and how these perceptions affect the development of entrepreneurship education in schools. Using a qualitative approach, interviews were conducted with four principals, two high schools and two vocational schools. The results showed that the principals’ understanding of entrepreneurial competence concerned developing business units for school income. There were differences between the high school and vocational school principals’ perceptions of entrepreneurship education. In vocational schools, the focus was more on developing school production units, while in high schools, the entrepreneurship education was the addition to the local content curriculum through craftsmanship teaching to students. The study found that the schools have limited resources to enhance knowledge to put entrepreneurship education into practice. Entrepreneurship education was viewed as difficult to develop in general schools due to the high school curriculum that focused on academic knowledge, where, there is no subject directly related to entrepreneurship. Abstrak: Tujuan penelitian ini adalah untuk mengetahui persepsi kepala sekolah pada jenjang Pendidikan menengah atas dan bagaimana persepsi tersebut berdampak terhadap kurikulum Pendidikan kewirausahaan di sekolah. Penelitian ini menggunakan pendekatan kualitatif. Informan yang diwawancarai adalah 4 kepala sekolah, 2 kepala SMA, dan 2 kepala SMK. Pemilihan kepala sekolah dilakukan berdasarkan jenis sekolah, SMA dan SMK. Hasil penelitian menunjukkan persepsi kepala sekolah tentang kompetensi kewirausahaan adalah tentang pengembangan unit bisnis sebagai sumber pendapatan sekolah. Terdapat perbedaan antara SMA dan SMK tentang pendidikan kewirausahaan. Di jenjang SMK, sekolah lebih fokus pada pengembangaan unit produksi dalam pengembangan kewirausahaan sekolah, sedangkan di jenjang SMA, pendidikan kewirausahaan dimasukkan dalam kurikulum muatan lokal dengan mengajarkan mata pelajaran prakarya pada peserta didik. Pendidikan Kewirausahaan juga dirasakan agak sulit untuk dikembangkan di SMA karena karakteristik kurikulum SMA yang dianggap lebih fokus pada pembelajaran yang sifatnya akademik, dan tidak adanya mata pelajaran khusus yang terkait langsung dengan kewirausahaan.